Self expanding stents for the management of aorto-ostial stenoses in saphenous vein bypass grafts. Issue 3 (September 1994) - Nordrehaug, J E; Priestley, K A; Chronos, N A; Rickards, A F; Buller, N P; Sigwart, U
Abstract : OBJECTIVE–To assess the early and follow up results of implantation of a self expanding stent in aorto-ostial stenoses of vein grafts. DESIGN–Prospective, non-randomised, observational study. SETTING–Tertiary referral centre for cardiac diseases. PATIENTS–Nineteen patients with ostial stenoses of saphenous vein grafts. MAIN OUTCOME MEASURES AND RESULTS–Stents were successfully deployed in all 19 patients with satisfactory angiographic results. In one patient this required two attempts. There were no deaths and no major procedural complications related to ostial stenting. Before discharge two (11%) patients had thrombosis of the ostial stent; one patient had a Q wave myocardial infarction. Femoral artery bleeding occurred in three (16%) patients. Angiographic follow up was performed in 18 patients at a mean of seven months. Restenosis within the ostial stent was detected in three (16%) patients. Twelve (63%) patients had an improved functional status at a mean follow up of nine months. One patient died suddenly at three months. Three (16%) patients required additional revascularisation procedures because of symptoms caused by restenosis within the ostial stent during follow up. CONCLUSIONS–Intracoronary stenting is an attractive treatment for the management of patients with vein graft ostial stenoses.